New apterous Carventinae from Sri Lanka and Southern India (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst; Baňař, Petr (Zootaxa, 2013)
Two new species of apterous Carventinae are described in this paper. One belongs to the endemic monotypic genus Singhalaptera Heiss 2001 from Sri Lanka (Singhalaptera secunda n.sp.), and the other to the monotypic genus Signocoris Hoberlandt 1958 from Madras (Signocoris nilgiricus n.sp.). All four known species of both genera are illustrated and compared.